Approaches to the formation of the cost of construction works performed by domestic construction companies outside Ukraine - Zakorko, P.; Vershigora, D.; Babiychuk, P. (Ways to Improve Construction Efficiency, 2018)
The article defines approaches to the formation of the cost of construction works performed by domestic construction companies outside Ukraine. The authors conclude that the formation of a competitive price for finished construction products or for separate construction works (services) abroad is often associated with the emergence of additional costs incurred by the contractors due to the specifics of exports (for travel, accommodation, transport costs for the delivery of construction equipment , costs for obtaining various approvals and permits, etc.).